Association of dietary and genetic factors related to one‐carbon metabolism with global methylation level of leukocyte DNA - Ono, Hiroe (John Wiley and Sons Inc., 2012)

(untitled) (Cancer Sci)
Global hypomethylation of leukocyte DNA has been associated with an increased risk of cancer. As dietary and genetic factors related to one‐carbon metabolism may influence both the methylation and synthesis of DNA, we investigated associations between these factors and the global methylation level of peripheral blood leukocyte DNA based on a cross‐sectional study of 384 Japanese women. Dietary intake of folate and vitamins B2, B6, and B12 was assessed with a validated semiquantitative food frequency questionnaire. Five polymorphisms in methylenetetrahydrofolate reductase (MTHFR) (rs1801133 and rs1801131), methionine synthase (MTR) (rs1805087), and methionine synthase reductase (MTRR) (rs10380 and rs162049) were genotyped. Global DNA methylation of leukocyte DNA was quantified using Luminometric Methylation Assay. A linear trend of association between methylation and dietary and genetic factors was evaluated by regression coefficients in a multivariable linear regression model. Mean global methylation level (standard deviation) was 70.2% (3.4) and range was from 59.0% to 81.2%. Global methylation level significantly decreased by 0.36% (95% confidence interval, 0.03–0.69) per quartile category for folate level. Subgroup analysis suggested that alcohol drinking modified the association between folate intake and global methylation level (P (interaction) = 0.01). However, no statistically significant association was observed for intake of vitamins B2, B6, and B12, alcohol consumption, or five single nucleotide polymorphisms of MTHFR,MTR, and MTRR. We found that higher folate intake was significantly associated with a lower level of global methylation of leukocyte DNA in a group of healthy Japanese females.